TINDAK TUTUR DIREKTIF DAN EKSPRESIF DALAM NOVEL TEMAN HIDUP KARYA ANDARU INTAN - Abd Salim Marna; Patriantoro Patriantoro; Agus Wartiningsih (Universitas Tanjungpura, 2019)
AbstractThis research talked about the speech acts in novel Teman Hidupby Andaru Intan.The speech act is the directive and expressive speech act that takes place between dialogues in novel Teman Hidup by Andaru Intan.The method used in this research is descriptive method. This research is in the form of qualitative research.The data source in this study is novel Teman Hidup by Andaru Intan.The data in this study are directive and expressive speech acts of speech. Data collection techniques used in this study are documentary study techniques. Techniques to test the validity of the data in this study are the perseverance of observation and the scope of the reference. The results of this study are utterances spoken by all figures both directive and expansive.The results of this study can be implemented in Indonesian language learning.Keywords: Expressive,Directive, Novels